Karl Polanyi Menanam Ekonomi - B Herry Priyono (Center for Philosophy and Ethics, 2010)
Karl Polanyi dikenal sebagai teoritikus ekonomi sosial yang menggagaskonsep ketertanaman ekonomi. Konsep tersebut dipaparkan dalam bukunya yangsangattermasyhur berjudul The Great Transformation (1944) sebagai titik sentraldalam bidang sosiologi ekonomi. Bernard Barber mengkritik konsep ketertanamanekonomi Polanyi sebagai konsep yang ambigu dan karenanya tidak dapat menjadisubjek utama dalam pemikiran ekonomi. Namun demikian, ketika menulis karyaThe Great Transformation, Polanyi menjelaskan terjadinya proses komodifikasi atasuang, tenaga kerja, dan tanah. Gagasan keternanaman ekonomi bersamaan dengankonsepnya mengenai gerakan-balik memiliki urgensi pada konteks ini, dan karena itukaryanya memiliki motif moral untuk menyelamatkan masyarakat. Karl Polanyi has been recognized as a social-economic theorist for his conceptof embedded economy. The concept was well-organized in his book The Great Transformation(1944) as the central point for the field of economic sociology. Bernard Barbercriticized Polanyi’s concept of embedded economy as something ambiguous and thus itcannot become the subject in the same theoretical scrutiny as other classic works in thefield. For Barber, all economies are embedded and therefore there are central tensionsand complexities concerning land, money, and labour in Polanyi’s argument that must beclarified. However, as he was writing the book, he developed several new concepts, includingfictitious commodities and embedded economy, that led in new directions to morality.The prospect is to create the conditions of the possibility to balance economic interests infinancial sector with social interests in the real sectors. This is the meaning of double movement,that is, to deliberate the market in order to save society.